An Experimental Study on Effectiveness of Cooperative Learning Strategy on Achievement in Economics Among the Higher Secondary School Students - . S, Priya; Vasimalairaja, M. (Journal of Ecohumanism, 2025)
The research article focuses its attention on the effectiveness of cooperative learning strategies on the achievement of higher secondary school students in Economics. For this, the investigator used experimental method of research. The students are classified into two equated groups one is for control group and another one is for experimental group, and among which, 50 are selected for control group and 50 are selected for experimental group. In every group equal representation of male and female categories of students. Moreover, they are further classified into three, namely low, average and high achievers. The control group is treated with traditional teaching procedure and the experimental group is treated with three cooperative learning strategies namely, JIGSAW, Group Investigation and Think-Pair-Share. For data collection, the investigator prepared and validated an achievement test in Economics. For data analysis, the investigator used ’t’ test. The findings of the experimental study revealed that the experimental group students are significantly higher than the control group students in their achievement in Economics.